Laborer's Working Hours, Work Stress, Recovery and Health in West Java: A Qualitative Study - Silvy Sondary Gadzali; A. Moeslihat Komara; Kamal Ma’ruf (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The study aims to explain the relationship between working hours and psychosocial work characteristics and review the health effects of working hours and related causes. It was identified that lack of sleep might affect work and working hours to illness. Provide an outline of the research method(s), data and materials used in this research. Explain how the method(s) is performed in order to obtain the results of discussions. It was identified that the most likely to improve recovery and health was through changes in working hours. Night work and shift work are associated with various health effects, the risk of morbidity being the most substantial evidence. Lack of sleep or insufficient sleep, associated with inadequate recovery, can cause long working hours, shift work, and work stress to illness. The best work-related mechanisms for reducing psychosocial workloads and the adverse health effects of working hours are regulating overtime and overworked hours, improving individual work-time control, improving recovery from sleep pattern recognition and promoting these principles into shift rotation.